PEMIKIRAN POLITIK SUTAN SJAHRIR TENTANG REVOLUSI - Maulana, Eko (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
The article describes SutanSjahrir’s struggle for the state and Indonesian people. Sjahrir’s struggle was grounded on democratic revolution and national revolution. The writer has formulated two main questions, are; first, how is the revolution of political parties wished by Sjahrir? Second, how did Sjahrir implement his idea about governmental revolution? The results of the study show that after Indonesianindependence, Sjahrir promulgated what so-called revolution of the political parties. To Sjahrir, the political parties should be in form of the cadres’ parties, not the masses parties. Furthermore, when dealing with the Indonesian governmental system, he contended governmental revolution. In this phase, Sjahrir stressed the importance of functioning of the civil service, police, and agrarian officers. He also called on the empowerment of workers and peasants through political education as democratic revolutionary forces.